A companion to music in sixteenth-century Venice - Schiltz, Katelijne, 1974- (Brill's companions to the musical culture of medieval and early modern Europe, 2018)
This book offers an overview of all facets of musical life in sixteenth-century Venice. It addresses the city's institutions (churches, confraternities, and academies) against the background of public and private occasions of music making. Supported by a generous collection of archival, literary, and iconographical sources, it treats both ceremonial life in the Serenissima and private forms of patronage. The Companion also addresses the dense web of musical activity (from chapel masters and singers to instrumentalists and instrument makers to music printers and theorists) and the rich variety of styles and musical genres (the frottola, the madrigal, motets and masses, instrumental music, polychoral music, Venetian-language polyphony), broadening the geographical perspective beyond the Veneto to Istria and Dalmatia. Contributors are Rodolfo Baroncini, Sherri Bishop, Bonnie J. Blackburn, David Bryant, Ivano Cavallini, Paolo Da Col, Daniel Donnelly, Rebecca Edwards, Iain Fenlon, Jonathan Glixon, Don Harrán (†), Jeffrey Kurtzman, Giulio M. Ongaro, Francesco Passadore, Elena Quaranta, Katelijne Schiltz, Eleanor Selfridge-Field, and Giovanni Zanovello.